Exploring the pandemic's potential effects on workers' collectivist values, prosocial behaviors, and attitudes toward mistreatment - Li, Ning; Liao, Huiyao; Pan, Jingzhou; Harris, T. Brad (Human Resource Management, 2022)
The global COVID‐19 pandemic has fundamentally changed the way we live and work in the short‐term, but history suggests that the crisis may also exert deeper, longer‐lasting effects. With the aim of providing preliminary insight into this possibility, we theoretically construct and empirically test hypotheses for how exposure to COVID‐19 stimuli (e.g., reading or watching media coverage, observing relief efforts) relates to the deep‐seated values that guide workers' attitudes and behaviors. Specifically, we build from prior work to posit that exposure to COVID‐19 stimuli is positively associated with workers' self‐transcendent prosocial values, which motivate prosocial behaviors directed toward society as a whole (i.e., charitable donations) and coworkers (i.e., helping). Extend the extant literature, we further argue that exposure to COVID‐19 stimuli will be positively associated with conservation values emphasizing self‐restraint, submission, protection of order, and harmony in relations, which in turn influences workers' willingness to tolerate mistreatment by authorities (i.e., abusive supervision, authoritarian leadership, exploitation). Evidence from 2,929 full‐time Chinese employees tracked for nearly 2 months and a diverse sample of 310 workers in the United States generally support our arguments, but also provide insight into potential cultural nuances.